Study of Bioefficacy and Phytotoxicity of Carfentrazone-ethyl 40% DF in Direct Seeded Rice - Shinde, V. V.; Jagtap, D. N.; More, V. G.; Mane, M. J.; Dademal, A. A. (International Journal of Bio-resource and Stress Management, 2018)
A field experiment was conducted at ARS, Repoli (180.18’ North latitude and 730.32’ East longitude), to study the bioefficacy and phytotoxicity of Carfentrazone-Ethyl40 % DF in direct seeded rice during Summer (January) of 2018. The field experiment was laid out in randomised block design with 14 treatments consists of Carfentrozone ethyl 40% DF @ 12.5 g ml-1 a.i. ha-1 at 20 DAS, Carfentrozone ethyl 40% DF @ 25 g ml-1 a.i. ha-1 at 20 DAS, Carfentrozone ethyl 40% DF @ 50 g ml-1 a.i.ha-1 at 20 DAS, Carfentrozone ethyl 40% DF @ 12.5 g ml-1 a.i.ha-1at 30 DAS, Carfentrozone ethyl 40 per cent DF @ 25 g ml-1 a.i. ha-1 at 30 DAS, Carfentrozone ethyl 40% DF @ 50 g ml-1 a.i.ha-1at 30 DAS, Carfentrozone ethyl 40% DF @ 12.5 g ml-1 a.i.ha-1 at 40 DAS, Carfentrozone ethyl 40% DF @ 25 g ml-1 a.i. ha-1 at 40 DAS, Carfentrozone ethyl 40% DF @ 50 g ml-1 a.i. ha-1 at 40 DAS, Carfentrozone ethyl 40% DF @ 25 g ml-1 a.i. ha-1 at 30 DAS (market product), Oxyflourofen 23.5% EC @ 150-240 a.i. ha-1 at 30 DAS, Bispyribac sodium 10% SC @ 20 g ml-1 ha-1 at 30 DAS, Untreated control and Hand weeding at 20 DAS and 40 DAS and three replications. Application of Carfentrozone ethyl 40% DF @ 25 g ml-1 a.i. ha-1 at 30 DAS recorded significantly higher grain and straw yield as compared to rest of the treatments under study as well as more weed control efficiency (86.19%) at harvest. No phytotoxicity effect was observed in any treatment after testing Carfentrozone ethyl 40% DF in direct seeded rice.